Leakage behaviour of elastomer seals under dynamic unloading conditions at low temperatures. (April 2017) - Grelle, Tobias; Wolff, Dietmar; Jaunich, Matthias
Abstract: In technical applications, static seals are sometimes also subjected to dynamic loadings. Therefore, the leakage behaviour under dynamic conditions has to be evaluated as well. For this purpose, FKM elastomer seals have been tested by using newly designed equipment that allows for rapid partial release of the seal and simultaneous leakage rate measurement at a wide range of test temperatures. Furthermore, material characterisation was done by using Dynamic Mechanical Analysis, Differential Scanning Calorimetry and Compression Set. It was shown that, under static conditions, the leakage rate increased significantly during cooling at temperatures around 18 K lower than the glass transition range. On reheating, the seal's functionality was restored in the high temperature region of the glass rubber transition. In the subsequent dynamic release tests, that comprised a reduction of the seal compression within 1 s from 25% to 23%, increased leakage rates were observed in the high temperature region of the glass transition range. It was shown that the temperature that is critical for increased leakage is significantly lower under static conditions compared to dynamic conditions. The obtained leakage rates for static tests and dynamic release tests at different temperatures were analysed with reference to results of the material characterisation.